2018
DOI: 10.3390/s18061956
|View full text |Cite
|
Sign up to set email alerts
|

Laser Self-Mixing Fiber Bragg Grating Sensor for Acoustic Emission Measurement

Abstract: Fiber Bragg grating (FBG) is considered a good candidate for acoustic emission (AE) measurement. The sensing and measurement in traditional FBG-based AE systems are based on the variation in laser intensity induced by the Bragg wavelength shift. This paper presents a sensing system by combining self-mixing interference (SMI) in a laser diode and FBG for AE measurement, aiming to form a new compact and cost-effective sensing system. The measurement model of the overall system was derived. The performance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Additionally, the maximum peak-peak value of the external cavity mode oscillation is about 0.056 as shown in (c), whereas the maximum peak-peak value of the relaxation oscillation is about 3.179 as shown in (a), more than 50 times larger than the external cavity mode oscillation. Figure 4(d) is the filtered SMI signal with a low-pass filter with cut-off frequency of 10 MHz, it can be seen from which the relaxation oscillation and external cavity mode oscillation are filtered, showing a conventional SMI as in the literature [5][6][7]. From above analysis, it can be concluded that there are two kinds of high-frequency oscillations in the SMI signals when the SMLD in moderate feedback regime with undamped RO.…”
Section: Simulation and Analysismentioning
confidence: 69%
See 2 more Smart Citations
“…Additionally, the maximum peak-peak value of the external cavity mode oscillation is about 0.056 as shown in (c), whereas the maximum peak-peak value of the relaxation oscillation is about 3.179 as shown in (a), more than 50 times larger than the external cavity mode oscillation. Figure 4(d) is the filtered SMI signal with a low-pass filter with cut-off frequency of 10 MHz, it can be seen from which the relaxation oscillation and external cavity mode oscillation are filtered, showing a conventional SMI as in the literature [5][6][7]. From above analysis, it can be concluded that there are two kinds of high-frequency oscillations in the SMI signals when the SMLD in moderate feedback regime with undamped RO.…”
Section: Simulation and Analysismentioning
confidence: 69%
“…However, the bandwidth of the trans-impedance amplifier is usually from several hundred KHz to several ten MHz, e.g. the detection circuit for conventional SMI signals in work [6,10] has a bandwidth of 10 MHz. Therefore, we apply a low-pass filter with cut-off frequency of 800 MHz and 10 MHz respectively on the SMI signal in Figure 3(b).…”
Section: Simulation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We call the laser diode in this case as optical feedback laser diode (OFLD) and the modulated intensity as OFLD signal. As a preferred, minimum part-count scheme useful for engineering implementation, various OFLD-based applications have been developed in the industrial and laboratory environment, such as measurement of displacement [7,8], vibration [9], velocity [10], alpha factor [11,12], Young's modulus [13], strain [14], acoustic emission [15], acoustic field imaging [16], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SMI-based sensing has been extended for material parameter measurement, acoustic detection and biomedical applications etc. [6,7]. When the injection current of the LD is modulated by a periodic triangular waveform, the phase of the detected SMI signal contains the micro-displacement of the external target.…”
Section: Introductionmentioning
confidence: 99%